The India-Myanmar Relationship: New Directions after a Change of Governments? - Pierre Gottschlich (International Quarterly for Asian Studies, 2018)
Despite a promising start after independence, bilateral relations between India and Myanmar have had a long history of mutual neglect and obliviousness. This paper revisits the developments since the end of colonial rule and points out crucial historical landmarks. Further, the most important policy issues between the two nations are discussed. The focal point of the analysis is the question of whether one can expect new directions in the bilateral relationship since the election of new governments in India in 2014 and in Myanmar in 2015. While there have been signs of a new foreign policy approach towards its eastern neighbour on the part of India under Prime Minister Narendra Modi, it remains to be seen if the government of Aung San Suu Kyi’s National League for Democracy will substantially alter Myanmar’s course on an international level.